Review article: controversies in the management of primary biliary cirrhosis and primary sclerosing cholangitis. Issue 3 (29th December 2013) - Karlsen, T. H.; Vesterhus, M.; Boberg, K. M.
Summary Background Despite considerable advances over the last two decades in the molecular understanding of cholestasis and cholestatic liver disease, little improvement has been made in diagnostic tools and therapeutic strategies. Aims To critically review controversial aspects of the scientific basis for common clinical practice in primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC) and to discuss key ongoing challenges to improve patient management. Methods We performed a literature search using PubMed and by examining the reference lists of relevant review articles related to the clinical management of PBC and PSC. Articles were considered on the background of the European Association for the Study of the Liver (EASL) and the American Association for the Study of Liver Diseases (AASLD) practice guidelines and clinical experience of the authors. Results Ongoing challenges in PBC mainly pertain to the improvement of medical therapy, particularly for patients with a suboptimal response to ursodeoxycholic acid. In PSC, development of medical therapies and sensitive screening protocols for cholangiocarcinoma represent areas of intense research. To rationally improve patient management, a better understanding of pathogenesis, including complications like pruritis and fatigue, is needed and there is a need to identify biomarker end‐points for treatment effect and prognosis. Timing of liver transplantation and determining optimal regimens of immunosuppression post‐liver transplantation will also benefit from better appreciation of pre‐transplant disease mechanisms. Conclusion Controversies in the management of PBC and PSC relate to topics where evidence for current practice is weak and further research is needed.